PELATIHAN PENGEMBANGAN PEMBELAJARAN BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) BAGI GURU BAHASA LAMPUNG JENJANG SMA Se-KOTA BANDARLAMPUNG - Tuntun Sinaga; Eka Sofia Agustina; Khoerotun Nisa Liswati (Universitas Lampung, 2022)
The purpose of this community service is to improve the ability of Lampung Language Subject Teachers throughout Bandar Lampung City in managing HOTS-based learning (Higher Order Thinking Skills). The methods used in this training are lectures, questions and answers, discussions, demonstrations, and assignments. The target participants in this training are 30 teachers, but in practice, the number of participants involved in this training activity is 8 teachers. This activity was carried out at SMA YP Unila for three days in October 2021. Furthermore, this HOTS-based learning development training implemented active training, in which all participants learned through their experiences so that the planned goals could be obtained optimally. This training uses a practical approach through guided training. The results of this service indicate that the HOTS learning development training for Lampung Language Teachers shows an enthusiastic attitude and increased ability to develop HOTS-based Lampung language learning tools.Keywords: hots (higher order thinking skills); lampung language; learning toolsAbstrakTujuan pengabdian kepada masyarakat ini adalah meningkatkan kemampuan para Guru Mata Pelajaran Bahasa Lampung se-Kota Bandar Lampung dalam mengelola pembelajaran berbasis HOTS (Higher Order Thinking Skills). Metode yang digunakan dalam pelatihan ini adalah ceramah, tanya jawab, diskusi, demonstrasi, dan pemberian tugas. Adapun target peserta dalam pelatihan ini adalah 30 guru, tetapi dalam pelaksanaannya jumlah peserta yang terlibat dalam kegiatan pelatihan ini berjumlah 8 guru. Kegiatan ini dilaksanakan di SMA YP Unila dalam tiga hari pada bulan Oktober 2021. Selanjutnya, pelatihan pengembangan pembelajaran berbasis HOTS ini menerapkan pelatihan aktif, yakni seluruh peserta turut belajar melalui pengalamannya sehingga tujuan yang telah direncanakan dapat diperoleh secara optimal. Pelatihan ini menggunakan pendekatan praktik melalui pelatihan terbimbing. Hasil pengabdian ini menunjukkan bahwa pelatihan pengembangan pembelajaran HOTS bagi Guru Bahasa Lampung menunjukkan sikap antusias dan meningkatnya kemampuan dalam menyusun perangkat pembelajaran bahasa Lampung yang berbasis HOTS.DOI: https://doi.org/10.23960/rp/v2i1.hal.48-55